CARDIOVASCULAR DISEASE RISKS AND FACTORS INFLUENCING THEM AMONG MEDICAL COLLEGE STUDENTS - Geske, Rita; Leice, Alevtīna; Miķelsone, Madara (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The aim of the study is to identify the CVD risks among medical college students associating them to their lifestyle. It should be noted that cardiovascular diseases also affect young people, which students are also. Information obtained during research is necessary for prospective medical staff to acknowledge their cardiovascular health and its influencing factors, as well as for college lecturers to make changes in study programs. The theoretical part of the research discusses various CVD risk determination methods, as well as lifestyle`s impact on cardiovascular health. The empirical part of the research contains information about ten years CVD risk among students, using two Framingham methods (based on the body mass index and amount of lipids in the blood) and seven risk factor (blood pressure, body mass index, smoking, total cholesterol, triglycerides, high-density cholesterol and glucose) addition method.